Human Leukocyte Antigen Type and Posttransplant Lymphoproliferative Disorder. Issue 6 (June 2015) - Lustberg, Mark E.; Pelletier, Ronald P.; Porcu, Pierluigi; Martin, Stanley I.; Quinion, Carl D.; Geyer, Susan M.; Caligiuri, Michael A.; Baiocchi, Robert A.
Abstract : Background: Posttransplant lymphoproliferative disorder (PTLD) is an infrequent but serious complication of solid organ transplantation. Early detection and initiation of therapy may improve outcomes. The purpose of this study was to identify human leukocyte antigen (HLA) type as risk and prognostic factors for PTLD. Methods: A review was undertaken to identify PTLD cases treated at our institution over the past 25 years. Logistic regression and Cox Proportional Hazards were used to model risk factors for PTLD and clinical outcomes in patients with PTLD. Results: One hundred six cases of PTLD were identified with 1392 solid-organ transplant recipient controls. Epstein-Barr virus (EBV) seronegative status pretransplant (odds ratio [OR] = 7.61, 95% confidence interval [95% CI] = 3.83-15.1) and receipt of a nonkidney transplant were associated with an increased risk of PTLD. Being African American and receipt of a living-related kidney transplant were associated with a decreased risk of PTLD. The HLA-B40 group was a risk factor for PTLD in EBV-seronegative individuals (OR = 8.38, 95% CI = 2.18-32.3), whereas HLA-B8 was a risk factor for PTLD in EBV-seropositive individuals (OR = 3.29, 95% CI = 1.52-7.09). Specific HLA types were not associated with graft failure or mortality after PTLD diagnosis. In PTLD patients, central nervous system (CNS) involvement, bone marrow involvement, T-cell PTLD, and age were associated with increased mortality. Conclusion: Human leukocyte antigen-B40 group and HLA-B8 were identified as novel susceptibility factors for PTLD in EBV-seropositive and EBV-seronegative individuals, respectively. Multicentered, large prospective studies of PTLD with correlative immunologic work are needed to test the significance of these observed associations. Abstract : This large, single-center retrospective study identifies important associative factors for posttransplant lymphoproliferative disorder. A novel association with HLA-B is noted suggesting the need for larger, confirmatory studies. Supplemental digital content is available in the text.